1992
DOI: 10.1080/0260137920110204
|View full text |Cite
|
Sign up to set email alerts
|

The educational affinities of old age and youth‡

Abstract: Too much emphasis on 'growing old' in our society has apparently been undermining the attitudes of late-life learners to 'keep growing'. By focusing on the planning context and client system components of basic programme planning, this paper explores the paradox that older adults and younger adults are too often segregated in their educational pursuits. While adult educators may be well aware of the older adult potential to learn, an unnecessary bias toward separate programming for younger and older learners p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…More attention to gender-specific educational needs of midlife and older adults is needed. Limited educational opportunities, higher poverty rates, and a longer life expectancy among women suggest they warrant attention in educational efforts (Girton, 1995;Harold, 1992;O'Brien, 1992); yet, as indicated here, men also may have specific family life education needs and should not be ignored.…”
Section: Implications For Family Life Educationmentioning
confidence: 96%
See 1 more Smart Citation
“…More attention to gender-specific educational needs of midlife and older adults is needed. Limited educational opportunities, higher poverty rates, and a longer life expectancy among women suggest they warrant attention in educational efforts (Girton, 1995;Harold, 1992;O'Brien, 1992); yet, as indicated here, men also may have specific family life education needs and should not be ignored.…”
Section: Implications For Family Life Educationmentioning
confidence: 96%
“…Education can be thought of as one way to meet the needs of people at different stages of life; focusing on one particular age group may neglect the benefits of intergenerational programming. Additionally, programs designed specifically for older adults may only serve to isolate this population (O'Brien, 1992). Sork (1988) raised ethical considerations by suggesting that the act of conducting a needs assessment may be interpreted by members of the target population to mean that all of the needs identified will be met.…”
Section: Limitationsmentioning
confidence: 99%
“…Indeed, there is no reason to believe that elderly individuals are incapable of learning, even though many researchers nd that uid intelligence (e.g., reaction time and a general ability to solve abstract problems) decreases in old age (Baltes, 1993;Baltes & Staudinger, 1993;Glendenning, 1995;Moody, 1986;Shuldiner, 1992;Willis, 1985). But as longitudinal studies have shown, the potential for learning remains intact throughout the life time as long as cognitive functioning is not affected by neurophysiological diseases, such as Alzheimer's (Mason, 1974;O'Brien, 1992;Shuldiner, 1992;Thornton, 1986;Willis, 1985).…”
Section: Ardeltmentioning
confidence: 99%
“…There is a general consensus that lifelong learning and continued education for older persons are essential in a society that is characterized by rapid technological changes (Glendenning, 1995;Moody, 1986;O'Brien, 1992;Thornton, 1986;Willis, 1985). A case in point is computer literacy without which people cannot participate in the current ''communication and information revolution'' (vide Moody, 1986).…”
Section: Ardeltmentioning
confidence: 99%
“…Tikkanen and Nyhan [10] argue that, in responding to support for seniors' learning, "… society, work organisations and individuals must think of ageing as a lifelong learning and developmental process in which one continuously takes on new challenges in line with one's interests, opportunities and limitations" (p3). However, while governments direct ongoing and explicit attention to supporting learning opportunities for younger and middle age groups, there remains a general and ongoing lack of understanding of, and investment to support appropriate learning opportunities for older Australians [11][12][13][14].…”
Section: Introduction the Context For Ageing And Learning In Australiamentioning
confidence: 99%